Percutaneous cementoplasty for painful osteolytic distal femur metastases: a case report - Lei M; Liu Y; Yang S; Jiang W; Cao Y; Liu S (Journal of Pain Research, 2016)
Mingxing Lei,1 Yaosheng Liu,1 Shaoxing Yang,2 Weigang Jiang,1 Yuncen Cao,1 Shubin Liu1 1Department of Orthopedic Surgery, 2Department of Pulmonary Neoplasms Internal Medicine, The Affiliated Hospital of Academy of Military Medical Sciences, Beijing, People’s Republic of China Abstract: Percutaneous cementoplasty has been shown to immediately restore the mechanical stability of affected bones, prevent further risk of bone fractures, and allow immediate weight bearing. It is emerging as one of the most promising procedures for patients with painful bone metastasis who are unsuitable for surgery or who show resistance to radiotherapy and/or analgesic therapies. This study aimed at describing the procedure, indications, and benefits of percutaneous cementoplasty for painful osteolytic distal femur metastases. We report the case of a painful metastatic lesion in the left distal femur secondary to non-small-cell lung cancer in a 58-year-old woman. The patient underwent percutaneous cementoplasty and experienced effective pain relief and recovery of knee function postoperatively. In addition, no perioperative complication was observed. Percutaneous cementoplasty for osteolytic distal femur metastases offers effective pain relief and restores impaired knee function. Although this method may be a safe option, larger samples of retrospective or prospective confirmation are warranted. Keywords: minimally invasive procedure, percutaneous cementoplasty, bone metastasis, distal femur